From Uncertainty to Trust: Enhancing Green Financing in the Agricultural Sector Through Accountability and Transparency (A Case Study of Bank XYZ) - Pamungkas, Wisnu; Juanda, Ahmad; Leniwati, Driana (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study examines the role of governance in green credit schemes, specifically focusing on how effective governance can reduce information asymmetry and enhance micro-agricultural enterprises' access to green financing. It also explores the potential of technologies such as blockchain and alternative credit scoring to improve governance and transparency in these schemes, aiming to contribute to the development of more effective policies for sustainable agriculture. This study explores governance in the green credit at Bank This study examines how governance can build trust in green financing through accountability and transparency, focusing on the challenges faced by micro agricultural enterprises in accessing credit. Information asymmetry between lenders and borrowers creates significant barriers, undermining trust and good governance in green financing. The study recommends enhancing understanding of credit scoring systems, improving communication, increasing transparency in evaluation processes, and implementing accessible appeals mechanisms. By addressing these challenges, Bank XYZ can improve stakeholder trust and strengthen governance in its green financing initiatives for the agricultural sector. Keywords: Accountability, Governance, Green Finance, Information Asymmetry, Transparency